Influence of prednisone on serum level of tumor necrosis factor alpha, interferon gamma and interleukin-1 beta, in active pulmonary tuberculosis - Rybacka-Chabros, Barabara; Pietrzak, Aldona; Milanowski, Janusz; Chabros, Paweł (Polish Journal of Public Health, 2014)
Introduction. Tumor necrosis factor alpha, interferon gamma and interleukin-1 beta modulate the interaction between T-cells and macrophages and play the key role in immune defense in Mycobacterium  tuberculosis infection. Several studies have demonstrated that corticosteroids may improve clinical conditions of patients with active pulmonary tuberculosis.Aim. The aim of the study was a potential impact of prednisone on the early immune response in HIV-negative young adults with active pulmonary tuberculosis, during the first four weeks of treatment.Material and methods. The study included 38 adults, aged 18-39 years, with active pulmonary tuberculosis. The first group of patients received only anti-tuberculosis chemotherapy whereas the second group of patients was administered antituberculosis chemotherapy and 20 mg prednisone, once daily. Serum levels of tumor necrosis factor-alpha, interferon-gamma and interleukin 1-beta were measured using ELISA kits before treatment initiation as well after two and four weeks of treatment, in both study groups.Results. The highest serum levels of evaluated cytokines were observed before treatment initiation. Serum levels of cytokines were significantly decreased in patients who received anti-tuberculosis drugs and prednisone, compare to those not treated with prednisone (p